2012
DOI: 10.1007/bf03404061
|View full text |Cite
|
Sign up to set email alerts
|

Risk Indicators and Outcomes Associated With Bullying in Youth Aged 9–15 Years

Abstract: Bullying is a form of aggression in which children are intentionally intimidated, harassed or harmed. The key elements of bullying include aggression, repetition and an imbalance of power between the bully and the victim. 1 Bullying can impact the physical, emotional and social health of a child. One literature review reports that victims of bullying are more likely to report sleep disturbances, abdominal pain, headaches, sadness, low self-esteem, depression, anxiety and suicidal thoughts. 1 A Canadian study r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
23
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(32 citation statements)
references
References 7 publications
7
23
0
2
Order By: Relevance
“…Similar studies revealed that boys were physically bullied more than girls and that boys were at higher risk of bullying than girls (22,26,49). Verbal bullying through mocking, relational attacks, and social exclusion were observed more frequently among girls than boys (22,38,49). The results of this study are similar to those in the literature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar studies revealed that boys were physically bullied more than girls and that boys were at higher risk of bullying than girls (22,26,49). Verbal bullying through mocking, relational attacks, and social exclusion were observed more frequently among girls than boys (22,38,49). The results of this study are similar to those in the literature.…”
Section: Discussionsupporting
confidence: 87%
“…By comparison, girls were more exposed to verbal and relational bullying and social exclusion than boys (Table VI). Similar studies revealed that boys were physically bullied more than girls and that boys were at higher risk of bullying than girls (22,26,49). Verbal bullying through mocking, relational attacks, and social exclusion were observed more frequently among girls than boys (22,38,49).…”
Section: Discussionmentioning
confidence: 77%
“…The results obtained on face-to-face bullying confirm the studies finding that bullying victims suffer from depression (Lemstra et al, 2012;Price et al, 2013), although they contradict the results of the study by Forlim et al (2014), who did not find depression in pure victims, although aggressive-victims did present depression. The discrepant results of the Forlim et al's (2014) study may be related to the characteristics of their sample because their participants presented high social vulnerability.…”
Section: Discussionsupporting
confidence: 64%
“…In general, studies have shown that victims of bullying present more physical and psychosomatic problems (Cassidy, 2009;Fekkes, Pijpers, Frediks, Vogels, & Verloove-Vanhorick, 2006;Modin, Låftman, & Östberg, 2015;Vernberg, Nelson, Fonagy, & Twemlow, 2011), more depression (Lemstra, Nielsen, Rogers, Thompson, & Moraros , 2012;Price, Chin, Higa-McMillan, Kim, & Frueh, 2013), suicidal ideation (Hinduja & Patchin, 2010), anxiety (Price et al, 2013), social anxiety (Pabian & Vandebosch, 2016), self-perceived stress (Williams, Turner-Henson, Davis, & Soistmann, 2017), low academic performance (Garaigordobil, 2013), and more mental health problems (Bannink, Broeren, van de Looij-Jansen, de Waart, & Raat 2014). Nevertheless, the study of Forlim, Stelko-Pereira, and Williams (2014) did not find depression in pure victims, although it did find depressive symptoms in aggressive-victims.…”
mentioning
confidence: 99%
“…Studies have demonstrated an increased prevalence of bullying in disadvantaged neighborhoods. 111118 Similarly, there is a higher risk of behavioral problems associated with unfavorable neighborhood conditions. 63 A higher level of social support in a friendly neighborhood may lower involvement in bullying.…”
Section: Bullying: Definitions Presentations and Epidemiologymentioning
confidence: 99%